2004
DOI: 10.1007/s10641-004-0101-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and population structure of the bayou darter, Etheostoma rubrum: disjunct riffle habitats and downstream transport of larvae

Abstract: SynopsisThe bayou darter, Etheostoma rubrum (Percidae), is endemic to the Bayou Pierre system in Mississippi. Adult and juvenile E. rubrum occupy swift, shallow riffles or runs over coarse gravel and pebble substrata. Habitat requirements of larval and post-larval stages, and the role of downstream dispersal of larvae in colonizing riffles are poorly known. The potential for movement and the high level of habitat specificity for the discontinuous riffle habitat suggest that E. rubrum may comprise a metapopulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Similarly, Stauffer et al (1996) found that darters showed the greatest specialization during the month with the greatest habitat availability. Finally, Bayou, orangefin and spotted darters displayed similar habitat use patterns to darters in Cloud's Creek with non-random use occurring along a substratum size and depth gradient (Kessler and Thorp 1993;Slack et al 2004). Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, Stauffer et al (1996) found that darters showed the greatest specialization during the month with the greatest habitat availability. Finally, Bayou, orangefin and spotted darters displayed similar habitat use patterns to darters in Cloud's Creek with non-random use occurring along a substratum size and depth gradient (Kessler and Thorp 1993;Slack et al 2004). Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Juveniles and larvae may actively move only limited distances, given their limited energy stores. However, darter larvae are common in the drift in some rivers (Turner 2001;Slack et al 2004), and perhaps accomplish much of their lifetime dispersal in that life stage. Our results are also limited to the early summer-early fall time period, the life stage between breeding and over-wintering.…”
Section: Discussionmentioning
confidence: 99%
“…The patchy distribution of critical habitat and fish across the landscape of a river network, or ''riverscape'' (sensu Fausch et al 2002), means that fragmented metapopulations can form within those networks (Rieman and Dunham 2000, Koizumi and Maekawa 2004, Slack et al 2004 introduced predatory fish may also be an important driver of such metapopulations, as they can fragment populations of vulnerable fish species (Labbe and Fausch 2000). Introduced fish have had severe impacts on native freshwater fish species around the world, sometimes resulting in local extinctions (Witte et al 1992, Lintermans 2000, Woodford et al 2005, and generally increasing overall extinction risks by fragmenting populations (Labbe andFausch 2000, Fagan 2002).…”
Section: Introductionmentioning
confidence: 99%